The Indicators of Bad Selection in Private Organizations of Bangladesh - Tamzid , Mohammad (South Asian Journal of Social Sciences and Humanities, 2022)
Purpose: The aim of this study is to recognize bad selection or wrongly selected employee in the organization. To do so, a variety of signs or symptoms of bad selection were described and closely reviewed in the literature. Methodology: To quantify and discover various measures of bad selection, this study used survey methodology. Questionnaire was prepared form the construct of the literature review. Cochran's formula was used to determine the adequacy of sample size to find out the authentic result. From various Bangladeshi private organizations, a total of 418 responses were obtained from people who are involved in employee selection process for the 2020-21 year. To analyze the data frequency analysis was done for the close ended questions and content analysis was done for one open ended question. Findings: On an average 6.09 alternatives have been chosen by the respondents from the given list of indicators of wrong hire. The finding also shows some other indicators to recognize bad selection, are offensive demeanors, apathy, and failure to lead. Originality/Value: This research demonstrates that organizations have to be careful about the signs of bad selection or wrong hire. Timely identification of the bad selection can help organization to take remedial steps and mitigate the negative consequences throughout the organization. This research may help organization to understand different indicators of bad selection
Keywords: Bad selection; Bangladesh; human resource management; private organization